PEMETAAN AIR TANAH MENGGUNAKAN METODE RESISTIVITAS WENNER SOUNDING (Studi Kasus Kampus II Universitas Islam Negeri Maulana Malik Ibrahim Malang) - Huda, A.M. Miftahul (Jurnal Neutrino, 2011)
Human is khalifa in this earth, it was presented at Qoran (Al-Fathir: 39). Then the  earth is authority and responsibility of human to saving and managing. Include of that is  aquifer. Aquifer is the water that is available in the throat of geology which permeable. The mapping of aquifer potency is important because it used for developing the collage II Islamic State University Maulana Malik Ibrahim of Malang at Junrejo, Batu. Good water is predicted consume at high level in future. This investigation purposefull to know the place of the potentiality of aquifer in the location of investigation verticality. The method used in this research is Resistivity Geoelectric is an used to investigate the current surface based on stone resistivity. In this  case,  is  used  wenner  sounding  configuration.  potentiality  of  aquifer  in  the location of investigation verticality. At the every measuring using resistivity meter OYO Mc 2119. The result of the survey show if variety of depth and thick layers of aquifer; whit the best potentiality of aquifer at sounding point 2 C C (7° 55' 11,9" LS dan 112° 32' 36,1" BT) in second line. Potency source of aquifer at hight more than 93,8 meter from surface. Then in first line, potency of aquifer is predicted bad. Cross-correlaton of sounding points showed that formation of geology is sands, sand- limestone, clay, and breccia.Kata Kunci: Qoran, Aquifer, Resistivity method of wenner sounding, Potency of Aquifer.